2023
DOI: 10.3389/fimmu.2023.1108116
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibody profiles in patients with immune checkpoint inhibitor-induced neurological immune related adverse events

Abstract: BackgroundNeurological immune-related adverse events (irAE-n) are severe and potentially fatal toxicities of immune checkpoint inhibitors (ICI). To date, the clinical significance of neuronal autoantibodies in irAE-n is poorly understood. Here, we characterize neuronal autoantibody profiles in patients with irAE-n and compare these with ICI-treated cancer patients without irAE-n.MethodsIn this cohort study (DRKS00012668), we consecutively collected clinical data and serum samples of 29 cancer patients with irA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 54 publications
(75 reference statements)
0
21
0
Order By: Relevance
“…Patients with neuromuscular disorders secondary to ICI agents are much more likely to have neuromuscular disease-specific antibodies compared with patients without ICI-related neuromuscular diseases. 12 In contrast, in a small sample of patients with irAE-MG, extensive evaluation of antibodies obtained from these patients were shown to be different from AChR antibodies from autoimmune MG in the degree and extent of complement fixation, raising questions about potential mechanisms of pathogenicity. 13 Although the potential side effects of PLEX, including coagulopathy and catheterrelated complications, should carefully be considered, the potential benefits of rapid recovery and steroid sparing effect may justify its use in severe neurologic syndromes.…”
Section: Discussionmentioning
confidence: 98%
“…Patients with neuromuscular disorders secondary to ICI agents are much more likely to have neuromuscular disease-specific antibodies compared with patients without ICI-related neuromuscular diseases. 12 In contrast, in a small sample of patients with irAE-MG, extensive evaluation of antibodies obtained from these patients were shown to be different from AChR antibodies from autoimmune MG in the degree and extent of complement fixation, raising questions about potential mechanisms of pathogenicity. 13 Although the potential side effects of PLEX, including coagulopathy and catheterrelated complications, should carefully be considered, the potential benefits of rapid recovery and steroid sparing effect may justify its use in severe neurologic syndromes.…”
Section: Discussionmentioning
confidence: 98%
“…The role of AChR Abs may also differ in ICI-related MG compared with typical idiopathic MG. For instance, in 2 of 3 seropositive patients with ICI-related MG evaluated by Masi et al, 21 the Abs did not activate complement or have modulating/blocking potency. The Abs could be an epiphenomenon because “neuromuscular antibodies” were detected in 15/24 (63%) patients with any type of immune-related adverse event versus 7% in controls in the study by Müller-Jensen et al 22…”
Section: Myasthenia Gravismentioning
confidence: 95%
“…It is clinically important that patients are evaluated for overlapping irMyositis and cardiomyositis. Overall, a retrospective cohort study of ICI-treated cancer patient with irNAE ( n = 29) and without ( n = 44) reported detection rates of up 80% of pathognomonic antibodies in patients suffering from irMyositis, irMyocarditis or irMG [18 ▪ ]. Routine autoantibody testing in suspicion of MG is warranted but nevertheless when negative, irMG can still be likely if typical clinical features and other supportive examinations findings are present [13].…”
Section: Immune Checkpoint Inhibitor-induced Myasthenia Gravis and My...mentioning
confidence: 99%
“…Routine autoantibody testing in suspicion of MG is warranted but nevertheless when negative, irMG can still be likely if typical clinical features and other supportive examinations findings are present [13]. Of note, some patients carry preexisting low-titre neuromuscular antibodies before initiation of ICI-treatment, which raises the question, if irNAEs evolve de novo or are triggered in the context of an underlying subclinical autoimmune disorder [7,16,18 ▪ ]. Compared to the classic form, irMG does not show a female preponderance (in younger patients) and occurs mostly in male, elderly patients (without associated thymoma) [19], and has a higher overall mortality.…”
Section: Immune Checkpoint Inhibitor-induced Myasthenia Gravis and My...mentioning
confidence: 99%